Behandlares, handledares och utbildares upplevelser av arbete med Emotion Regulation Group Therapy ur ett implementeringsperspektiv - Dimblad Gonzalez,Isabell; Victorén,Johanna (2024)
The integration and dissemination of a method within routine care rely not only on treatment efficacy but also on the effectiveness of the implementation. So far, Emotion Regulation Group Therapy (ERGT), a manual-based group treatment, has not been investigated from an implementation perspective. The aim of this study was to examine the implementation process of ERGT in Sweden and thereby contribute to a broader understanding of how the method functions in practice. This was examined through the research question: What possibilities and challenges do ERGT therapists, supervisors and educators describe from working with the method? Ten semi-structured interviews were conducted, and the data was analyzed using reflexive thematic analysis. Four themes were formulated: Adherence and adaptations, Challenges faced by ERGT therapists, The handling of the challenges and Contradictory notions about ERGT’s future. Respondents attest to the possibility to adhere to the treatment manual. Education and supervision can be used to overcome difficulties. Treatment fidelity along with aspirations to disseminate it exists. However, the method requires a high degree of therapeutic skills and challenges the therapist in terms of working with the manual, managing the time and maintaining a group processes. Additional and updated research on ERGT is requested. Our respondents paint a picture that the implementation process of ERGT, from a user’s perspective, has worked well so far. However, reasons for apprehensions about ERGT’s future exist. This can inspire future modifications and advancements in ERGT. The study exemplifies how implementation concepts can be applied when exploring treatment implementation.
Keywords: Emotion Regulation Group Therapy; implementering; möjligheter och utmaningar; behandlares upplevelser Emotion Regulation Group Therapy; implementation; facilitators and barriers; therapists’ experiences